Molecular typing of PPRV strains detected during an outbreak in sheep and goats in south-eastern Gabon in 2011 - Maganga, Gael D; Verrier, Delphine; Zerbinati, Rodrigo M; Drosten, Christian; Drexler, Jan F; Leroy, Eric M (Virology journal, 2013)
BACKGROUND: Peste des petits ruminanats (PPR) is an economically important viral disease affecting goats and sheep. Four genetically distinct lineages of peste des petits ruminants virus (PPRV) have been identified. In Gabon, the virus has not so far been detected. FINDINGS: Epidemiological investigations of Aboumi PPR outbreak revealed a high case fatality rate in sheep (98.9%). We detected and characterized peste des petits ruminants virus (PPRV), in October 2011, during the suspected outbreak in sheep and goats in Aboumi village located in the south-eastern. PPRV RNA was detected in 10 of 14 samples from three sick animals. Phylogenetic analysis revealed that the PPRV strain belonged to lineage IV and was closely related to strain circulating in neighboring Cameroon. CONCLUSIONS: This is the first molecular detection and typing of the PPRV strain associated with fatal PPR infection in these small ruminants and concrete evidence that PPRV is present and circulating in Gabon.